2013
DOI: 10.1017/s000711451200606x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of platelet aggregation-related eicosanoid production by dietary F-fucoidan from brown algaLaminaria japonicain human subjects

Abstract: Laminaria japonica is traditionally eaten in Japan as a beneficial food for thrombosis. The alga contains two specific ingredients, a xanthophyll fucoxanthin (FX) and a polysaccharide, F-fucoidan (FD). The aim of the present study was to investigate whether FX or FD exhibited anti-thrombotic effects. For this purpose, three types of capsules, containing 1 mg FX, 400 mg fucoidan, and both, were prepared from the alga and administered to volunteers for 5 weeks. The dose of FD or FD þ FX significantly shortened l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…We have also found that a dietary fiber, fucoidan, causes the secretion of hydrogen peroxide into blood by stimulating NADPH oxidase 1 in intestinal epithelial cells and increases PGI 2 in the blood. (50) An interesting point is that hydrogen peroxide is an inducer of PGI 2 production but 9-ONA is an inducer of TxA 2 , although both are produced in the cyclooxygenase pathway of the arachidonate cascade. The stimulating mechanism for the key enzyme of the arachidonate cascade PLA 2 should be examined in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that a dietary fiber, fucoidan, causes the secretion of hydrogen peroxide into blood by stimulating NADPH oxidase 1 in intestinal epithelial cells and increases PGI 2 in the blood. (50) An interesting point is that hydrogen peroxide is an inducer of PGI 2 production but 9-ONA is an inducer of TxA 2 , although both are produced in the cyclooxygenase pathway of the arachidonate cascade. The stimulating mechanism for the key enzyme of the arachidonate cascade PLA 2 should be examined in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…This study, realized on a small cohort of 14 men, suggested that a 1.5-g daily dose of a strong-gelling alginate limits glucose and cholesterol uptake, hence reversing hypercholesterolemia and diabetes mellitus symptoms and reducing CVD development risk. This treatment presented an antithrombotic effect monitored by an ex vivo global thrombosis test and measure of the thrombus lysis time (Ren et al, 2013). Alginate is widely utilized as a biomaterial for tissue engineering and regeneration because of its biocompatibility, nonthrombogenic nature, mild and physical gelation process, and the resemblance of its hydrogel matrix texture and stiffness to that of the extracellular matrix.…”
Section: Seaweed-extracted Molecules Polysaccharidesmentioning
confidence: 99%
“…Fucoidan, which is contained in Saccharina japonica, is exclusively composed of fucose and sulfated fucose. It was reported that fucoidan is hardly absorbed in intestinal tract and excreted in the feces [17]. A previous study reported that oral administration of fucoidan exhibited anti-allergic effects, whereas its intraperitoneal administration showed no effect [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fucoidan, a kind of sulfated polysaccharide obtained from some brown algae, is mainly composed of fucose and sulfated fucose and sometimes contains other sugars, such as mannose, glucose, galactose and xylose [13]. It has been shown that fucoidan exhibited various biological activities, such as antitumor, immunomodulatory [14][15][16], anti-thrombotic [17][18][19] and antioxidant activities [20]. Fucoidan, which is contained in Saccharina japonica, is exclusively composed of fucose and sulfated fucose.…”
Section: Introductionmentioning
confidence: 99%